Is Setting up Barriers to Entry Always Profitable for Incumbent Firms? - Dilek, Serkan; Top, Seyfi (Elsevier BV, 2012)
AbstractBarriers to entry have been subject to so many studies examining competition conditions and markets in industrial and micro economics literature. Markets with no entry barriers realize better performance and in these markets long run equilibrium actualized when average total costs equal to price. Generally firms can set up higher prices than their average total costs when entry is not free. Therefore incumbent firms prefer to set up entry barriers and avoid competition. However in two-sided markets new entrants can provide benefits to incumbent firms. So, in these conditions incumbent firms chose to reduce or eliminate barriers to entry. We examined this type of markets and their effects to market equilibrium and incumbent firms.
Keywords: Competition; Network Externality; Barriers To Entry; Two-Sided Markets; Barriers to Entry; 8. Economic growth